A theory of Abject Appearance: Women elite leaders' intra-gender 'management' of bodies and appearance. (May 2016) - Mavin, Sharon; Grandy, Gina
In this article, we develop a theory of Abject Appearance to explain women elite leaders' embodied identity work within a context of intra-gender relations. The theory of Abject Appearance illuminates a dynamic and dialectical process whereby women elite leaders 'manage' the ambiguities of their 'in-between' and 'abject' status. This process is understood as a possible material effect or consequence of women's abjection in organizations. Women elite leaders hold power through their formal positions, yet remain marginalized in social relations because their feminine bodies are out of place in organizations. In a qualitative study with women elite leaders, we illustrate how the theme Fascination with bodies and appearance depicts a dialectical process of simultaneous disgust and attraction with women's bodies and appearance. We discuss how this material effect of abjection may be played out through two embodied identity work strategies in an intra-gender context, namely: Shifting focus from the body and appearance and Achieving a professional balance . We offer insights into how women's embodiment in elite leader roles may be constrained in a context of intra-gender relations. We suggest opportunities to strengthen women's agency by raising awareness to the theory of Abject Appearance and women leaders' associated body work.